2014
DOI: 10.1093/ejo/cju083
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health during clear aligners treatment: a systematic review

Abstract: Periodontal health indexes were significantly improved during CAT. The results of this review should be interpreted with some caution because of the number, quality, and heterogeneity of the included studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 20 publications
3
89
0
4
Order By: Relevance
“…The primary factor is plaque accumulation, which is the main risk factor for periodontal diseases during orthodontic treatment. Rossini et al did a systematic review and concluded that periodontal health indexes were significantly improved during clear aligner treatment based on a moderate level of evidence for all the studies they selected (Rossini et al, ). In this study, we found that after 6‐month Invisalign treatment, the PI scores of patients significantly decreased, while BOP and PPD did not obviously change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary factor is plaque accumulation, which is the main risk factor for periodontal diseases during orthodontic treatment. Rossini et al did a systematic review and concluded that periodontal health indexes were significantly improved during clear aligner treatment based on a moderate level of evidence for all the studies they selected (Rossini et al, ). In this study, we found that after 6‐month Invisalign treatment, the PI scores of patients significantly decreased, while BOP and PPD did not obviously change.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed a growing number of orthodontic patients who seek Invisalign treatment for esthetic and convenience considerations. Moreover, it has been reported that compared to conventional fixed orthodontic treatment, Invisalign appliances do little harm to oral hygiene (Miethke & Vogt , Rossini, Parrini, Castroflorio, Deregibus, & Debernardi, ). A large amount of previous literature has shown that fixed orthodontic treatment poses a great threat to oral health of orthodontic patients, causing moderate to severe complications, such as white lesions, caries, periodontitis, and halitosis (Heymann & Grauer , Ren, Jongsma, Mei, Mei, & Busscher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant variable for microbiota alterations is the amount of time the appliance is worn in the oral cavity, with removable appliances having significantly less impact on oral bacteria than fixed appliances [61]. …”
Section: Discussionmentioning
confidence: 99%
“…Less devastating results from changes in the oral microbiota emerged from studies on functional appliances and on aligners, which are used up to 22 h a day [61]. So, it seems more important to be able to remove the appliance and wash both it and the teeth rather than the length of time the device is worn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the current concept of an optimal force in orthodontics is based on the theory that a force of a certain magnitude and duration would be capable of producing a maximum rate of tooth movement without tissue damage . Tooth movement with the Invisalign system is distance‐based, as opposed to forced‐based with the fixed appliance systems.…”
Section: Discussionmentioning
confidence: 99%